Effects of the stationary phase and the solvent on the stereodynamics of biphep ligands quantified by dynamic three-column HPLC* - Maier, Frank; Trapp, Oliver (Angewandte Chemie. International edition, 2012)
Dynamics and kinetics in a single stroke: The stereodynamics of the tropos-chiral diphosphine biphep and its 3,3′-dialkoxy analogues were investigated by enantioselective dynamic HPLC (DHPLC) and a novel three-column approach, in with the dynamics and kinetics of the interconversion were examined in a single experimental setup (see scheme).